Perhitungan Cost of Poor Quality pada PT Techwah Paper Products Indonesia Periode Tahun 2010-2011 - Arif Darmawan; Ratna Sumira (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2015)
This research was conducted at PT Teckwah Paper Products Indonesia with descriptive research method. The purpose of this study was conducted to determine how recording and rework calculations on the PT Techwah Paper Products Indonesiadan conformance with theory. This research was conducted on 5 February to 5 May 2014. The results showed that the cost of poor quality recording to rework foldingline and delamination in 2010 and 2011, is not in accordance with the theory that there is a difference in cost of rework of $ 60.26 is lower than that. The company should only consider direct labor costs but doesn’t take into account the material and overhead costs.